Efektivitas Bantuan Sosial Program Keluarga Harapan (PKH) di Kabupaten Magetan Berdasar Prinsip Keadilan dalam Islam - Ellyvia Abiyani; Endah Setyowati (Studia Economica : Jurnal Ekonomi Islam, 2025)
This study aims to analyze the effectiveness of the Program Keluarga Harapan (PKH) social assistance in Magetan Regency as an effort to overcome poverty and review the distribution of PKH social assistance from the perspective of justice in Islam. The distribution of PKH social assistance is expected to help the community meet its daily needs, thereby improving the community's standard of living and decreasing the prevalence of poverty. However, in practice, the distribution of social assistance has several obstacles so the main objective is not immediately achieved. This study uses a qualitative method with a literature study approach collaborated with field studies with data from the Ministry of Social Affairs as the main data source and supported by publications from other institutions and interviews with related institutions in Magetan Regency. The results of the study indicate that PKH social assistance is at an optimal level of effectiveness in overcoming poverty and needs to be improved again in order to achieve maximum effectiveness. The distribution of social assistance is not by one of the principles of Islamic economics, namely the principle of justice where there are KPM who do not receive assistance that should be their right so the PKH distribution mechanism needs to be reviewed. The research results can serve as a basis for improving the PKH program to be more effective in achieving poverty alleviation goals and help formulate more effective and sustainable poverty reduction policies in line with the principles of justice in Islam